(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: To date, there is no information on relationships of systemic (activation of the sympathoadrenal and renin- angiotensin systems, SAS and RAS, respectively) and local (inflammation and remodeling of the retinal extracellular matrix and activation of the ocular purinergic system) mechanisms of the development of diabetic maculopathy (DMP) and diabetic macular edema (DME). Purpose: To identify the influence of systemic and local factors of type 2 diabetes mellitus (DM) on functional status of platelets in DMP and DME under conditions of severe nonproliferative (NPDR) or proliferative diabetic retinopathy (PDR). Materials and Methods: This study included 42 type 2 DM patients (42 eyes), of which 31 patients (31 eyes) and 11 patients (11 eyes) were found to have DMP in the presence of PDR and severe NPDR, respectively. Platelet aggregation in vitro to ADP, adrenaline, angiotensin 2 (Ang2), platelet activation factor (PAF) and collagen were assessed spectrophotometrically with a Chrono-Log aggregometer. Results: As platelet hyperreactivity to AN II, adrenalin, PAF and collagen were found in all study patients, activation of the RAS and SAS, and inflammation and remodeling of retinal extracellular matrix are non-specific pathogenetic mechanisms of DMP. Platelet reactivity to ADP was higher in PDR than in severe NPDR (р=0.008), which reflected the features of the pathogenesis of PDR. Development of DME in patients with DMP could be caused by a pronounced dysregulation of purinergic signaling in the eye, activation of the RAS and inflammation, which was reflected by platelet hyperreactivity to ADP, AN II and PAF, whereas a high platelet reactivity to collagen was characteristic of the absence of DME. Conclusion: The analysis of functional status of platelets allowed elucidating platelet activation mechanisms and identifying major platelet agonists that enabled platelet involvement in progression of DMP and development of DME in type 2 DM patients with proliferative diabetic retinopathy.